Hotel promotion through social media: hotel Anantara Vilamoura & Algarve resort - Lousada, Inês (2021)
The main objective of the present study is to understand the role of networks in the promotion of the Hotel Anantara Vilamoura & Algarve Resort. In response to the objective research, the following specific objectives were considered: i) to identify social networks used by the hotel; ii) understand the monitoring that the hotel gives to social networks; iii) identify the social networks most used by customers; iv) identify problems and challenges faced by the hotel in the management of its social networks; v) understand how the hotel uses the networks to be more competitive. A qualitative methodology was applied supported by semi-structured interviews with the Hotel Director, the Head of Social Networks, and the Guests, between August and October 2020. The information on the interviews was handled individually through content analysis. It was concluded that the network services are a direct channel between the Hotel and consumers, which facilitates brand exposure and interaction with customers. In this regard, it allows for greater loyalty and to attract new customers. The results reveal that, when compared to other traditional means of communication, online social networks are a great tool that allows the hotel to publicize its services easily and quickly, in real-time, with great exposure and with reduced costs. The hotel is concerned to use social networks in the best way, with a focus on the current client and the target audience.